MEDIA PEMBELAJARAN BAHASA DAERAH AKSARA LONTARA BERBASIS MULTIMEDIA UNTUK PESERTA DIDIK KELAS III SEKOLAH DASAR NEGERI 29 BONTOMACINNA - Reni Anggraeni; Farida Farida; Muhammad Awal Nur (CV. LAJAGOE PUSTAKA, 2025)
This research aimed to: (1) Design multimedia-based Lontara script of local language learning media for the third grade students of Sekolah Dasar Negeri 29 Bontomacinna, (2) To find out the implementation of multimedia-based Lontara of locall language learning media for third grade students of Sekolah Dasar Negeri 29 Bontomacinna. This research used a multimedia development method, namely the multimedia development life cycle (MDLC). This research aimed to develop interesting and efficient learning so that it can increase the knowledge and interest in learning for students, which consisted of 6 stages namely concept, design, collection of materials, assembly, testing and distribution.The result of this research are (1) The design stage of multimedia-based Lontara script of Local language learning media for the third grade students of Sekolah Dasar Negeri 29 Bontomacinna was designed using the Unified Modeling Language (UML), namely, use case diagram, sequence diagram and activity diagram with making application using Adobe flash professional Cs6 and CorelDraw X7, (2) The learning media for the Local language of the Lontara script have been implemented by educators for the Third Grade students of Sekolah Dasar Negeri 29 Bontomacinna which can be used easily as new breakthrough in learning process, and validation has been carried out with the result of blackbox testing , all icons and buttons work according to their function. Testing the use of learning media applications using the System Usability Scale (SUS) method with a value of 72, it means the value scale is B or included in the Good category.